Role of Intrapersonal Communication on Human Development of Direct and Indirect Conflict Participants in Nepal - Acharya, Trishna (Bouddhik Abhiyan (बौद्धिक अभियान), 2022)
Human development of conflict participant during Nepal’s armed conflict started from 2052 BS has been studied in this research paper. Role of intrapersonal communication in difficult life condition (conflict) in human development of both direct and indirect conflict participant has been researched using qualitative research methodology taking human’s inward development factor as physiological, psychological, emotional, cognitive, and intellectual aspect as well as outward support system as social, economic, political, cultural, religious, technological and global system are taken as the variables. For this hermeneutic phenomenological qualitative study in-depth interview of 4 participants from direct and indirect conflict participant in Nepal is taken being based on interpretive research philosophy in a cross-sectional time frame adopting inductive approach. Major finding of this study is that healthy positive intrapersonal communication should be initiated by individual with active functionality of support system for individual’s growth to its fullest human potential for which constant communication with self is significant.